Exploring The Perspectives of Integrated Reporting for Future Research Opportunities - Chirata Caraiani; Camelia I. Lungu; Alina Luca; Cornelia Dascălu (Journal of Accounting and Management Information Systems (JAMIS), 2018)
This paper investigates the perspectives of integrated reporting as an emerging field in mainstream academic literature. The current state of research and its development are explored by using the Structured Literature Review (SLR) method on publications indexed in Clarivate Analytics' Web of Science. An analytical framework is designed for applying the coding procedure. The findings suggest an evolution of integrated reporting research from the phase of spreading awareness regarding the new reporting paradigm towards an impact analysis phase. The accounting and audit journals are noted to have greatly contributed to the shift of IR literature towards studying the integrated reporting as a reporting practice. A further purpose is to examine newly developed research interest in integrated reporting and to establish future paths to be followed. Future research might bring to discussion possible links between integrated reporting, governance and integrated thinking. The complex interrelationships influencing the companies' ability to create value for the multi-stakeholders need to frame the practice-oriented research.
Keywords: M14; M41; 650; Integrated reporting; structured literature review; IR literature; meta-analysis